Underdiagnosis and misclassification of COPD in Sweden: A Nordic Epilung study - Axelsson, Malin; Backman, Helena; Nwaru, Bright I.; Stridsman, Caroline; Vanfleteren, Lowie; Hedman, Linnea; Piirilä, Päivi; Jalasto, Juuso; Langhammer, Arnulf; Kankaanranta, Hannu; Rådinger, Madeleine; Ekerljung, Linda; et al. (Respiratory Medicine, 2023)
Introduction: The prevalence of COPD tends to level off in populations with decreasing prevalence of smoking but the extent of underdiagnosis in such populations needs further investigation. Aim: To investigate underdiagnosis and misclassification of COPD with a focus on socio-economy, lifestyle determinants and healthcare utilization. Method: The 1839 participants were selected from two ongoing large-scale epidemiological research programs: The Obstructive Lung Disease in Northern Sweden Studies and the West Sweden Asthma Study. COPD GOLD was defined according to the fixed post-bronchodilator spirometric criteria FEV1/FVC<0.70 in combination with respiratory symptoms. Results: Among the 128 participants who fulfilled the criteria for COPD GOLD , the underdiagnosis was 83.6% (n = 107) of which 57.9% were men. The undiagnosed participants were younger, had higher FEV1% of predicted and less frequently a family history of bronchitis. One in four of the undiagnosed had utilized healthcare and had more frequently utilized healthcare due to a burden of respiratory symptoms than the general population without COPD. Underdiagnosis was not related to educational level. Misclassification of COPD was characterized by being a woman with low education, ever smoker, having respiratory symptoms and having a previous asthma diagnosis. Conclusion: In the high income country Sweden, the underdiagnosis of COPD was highly prevalent. Reduced underdiagnosis can contribute to risk factor modification, medical treatment and self-management strategies in early stages of the disease, which may prevent disease progression and improve the quality of life among those affected. Therefore, there is a need to increase the use of spirometry in primary care to improve the diagnostic accuracy. Peer reviewed